Regulation of mTORC2 Signaling - Wenxiang Fu (Genes, 2020)
Mammalian target of rapamycin (mTOR), a serine/threonine protein kinase and a master regulator of cell growth and metabolism, forms two structurally and functionally distinct complexes, mTOR complex 1 (mTORC1) and mTORC2. While mTORC1 signaling is well characterized, mTORC2 is relatively poorly understood. mTORC2 appears to exist in functionally distinct pools, but few mTORC2 effectors/substrates have been identified. Here, we review recent advances in our understanding of mTORC2 signaling, with particular emphasis on factors that control mTORC2 activity.